PEMBUATAN BASIS DATA ALUMNI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS MATARAM - Lalu Japa; Gito Hadi Prayitno; I Gede Mertha (Postgraduate, University of Mataram, 2018)
The one form of a research as an advanced action suggestion of the research done by Handayani et al. (2013) was construction of a base data of alumni that could easily reach all alumni of Biology Education Study Program FKIP University of Mataram, as they are widely separated in some parts of Indonesian region. This descriptive research provided some explanation in relation to the profile of the alumni Biology Education Study Program FKIP University of Mataram. The alumni base data was constructed based on SQL. The result of research explained that the alumni base data using SQL program was very helpful for analysis of separation and various kinds job of alumni, so the Biology Education Study Program FKIP University of Mataram could do evaluation and developing as the needed of market or job market. This research also showed during the periods of 30 years, the alumni of Biology Education Study Program FKIP University of Mataram that work as a teacher with some fluctuation. There was 92% as a teacher for the alumni period 1980-1994, and slightly increased became 93% for alumni period 1995-2004, than decreased sharply became 54% during the period of 2005-2014.Keywords: Base Data, Alumni, Based on SQL